APLIKASI POWERSIM PADA SIMULASI DINAMIS RANTAI PASOK BAWANG MERAH DI KABUPATEN CIREBON - Wijaya, Wijaya; Yayat Rahmat Hidayat; Deden; Salim; Jian Fauzi Raisa Eliah (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2024)
ABSTRACT This research aims to find out the actors in the shallot supply chain, as well as finding the best scenario in the shallot supply chain in Cirebon Regency, in increasing the supply of shallots to meet consumer demand for shallots. To obtain data for analysis, this research uses a survey method by collecting data from each component in the shallot supply chain, as well as documentation studies that are relevant to the research objectives by collecting data from related agencies or institutions. The results of the research show that: (1) Actors or actors in the shallot supply chain in Cirebon district, West Java consist of producer farmers, collecting traders (middlemen), wholesalers, retailers and consumers, (2) The dynamic system of the shallot supply chain in Cirebon district, West Java consisting of a production subsystem, supply and delivery subsystem, and demand subsystem, and (3) Model simulation to be able to project the condition of the shallot supply chain in the next 10 years using scenarios of changes to the parameters of the percentage of shallots that are scattered and increasing shallot productivity